AUTHORITY OF LOCAL GOVERNMENTS IN MANAGEMENT RENEWABLE ENERGY : - , Ketut Krisna Hari Bagaskara P.; I Nengah Nuarta (Universitas Bali Dwipa, 2025)
Indonesia has faced various problems regarding the fulfillment of targets in energy development until now. Dependence on non-renewable energy is still high, causing the adequacy of energy reserves, especially in Indonesia, to still be highly dependent on the development of exploration. The legal rule of the authority of the regency/city local government to manage energy requires consistency in its implementation as stipulated in Article 14 paragraph 1 of the Local Government Law states that the determination of the division of government affairs in the fields of forestry, marine, and energy and mineral resources is divided into two, namely the Central Government and the Provincial Regions, in this case it clearly negates the autonomy of the Regency/City Regional Government. The authority of the provincial local government in the management of renewable energy Currently, the legal rules governing the authority of the central government in energy management are contained in Article 14 paragraph (1) and paragraph (3) of the Local Government Law. The authority of the regency/city local government in the management of renewable energy, the legal rules that regulate the authority of the provincial local government in energy management are contained in Article 26 paragraph (2) of the Energy Law. The lex specialis set of provisions or norms must be at a level (hierarchy) that is the same as the lex generalis set of provisions or norms. So it is clear that the City Government has the authority, namely attribution authority that comes directly from the legislation, because it is sourced directly from Article 26 paragraph 3 of the Energy Law.